Optimization of power generation and distribution for vertical farming with wireless sensor network (WSN) - Labrador, Cornelio G., II (Animo Repository, 2018)
Vertical farms were conceptualized to provide food security and as it requires power to operate, renewable energy source is an essential component. With photovoltaic cells as the main source, sufficient power storage will make sure to provide all power needed by plants. Automated mains grid switching can also make sure to provide the required energy to operate during rainy seasons and calamities. Utilizing excess energy by sharing to other farm does not only optimize power consumption to lower the cost, it will also support the campaign for lessening of carbon footprint. Because of this, this study proposes a solution for development and design of optimized power generation and distribution for the vertical farms. The sharing of excess energy of a node and switching to mains power grid will be decided though fuzzy logic control. Fuzzy logic control will be based on the state of charge (SoC) of each node. Wireless sensor network (WSN) will provide two-way communications between node and coordinator.